Kesalahan-kesalahan umum dalam shalat : lengkap dengan koreksinya / Abu Ammar Mahmud Al-Mishri; penerjemah, Zuhdi Amin, Muhammad Faiz - AL-MISHRI, Abu Ammar Mahmud; Zuhdi Amin; Muhammad Faiz (Darul Haq, 2015)
xxxviii, 358 hlm. ; 24 cm.